National trends and clinical outcomes of interventional approaches following admission for infected necrotizing pancreatitis in the United States. Issue 5 (20th May 2023) - Tran, Zachary; Xu, Jane; Verma, Arjun; Ebrahimian, Shayan; Cho, Nam Yong; Benharash, Peyman; Burruss, Sigrid
Abstract : An analysis using the National Inpatient Sample reveals that minimally invasive procedures (MIS) for infected necrotizing pancreatitis have increased over time. Compared to open approaches, MIS was associated with lower odds of in-hospital complications and resource use Abstract : BACKGROUND: With recent studies demonstrating the efficacy of minimally invasive approaches following infected necrotizing pancreatitis, latest guideline recommendations support their use. However, large-scale studies are lacking, and the national landscape following these guidelines remains poorly characterized. The present study examined trends in intervention strategies and the association of approach on clinical outcomes and resource use in a nationally representative cohort. METHODS: The 2016–2019 National Inpatient Sample was queried for adult hospitalizations for pancreatitis with infected necrosis. Patients were classified as drain only (DO) if they received only percutaneous or endoscopic drainage, minimally invasive (MIS) if they underwent endoscopic or laparoscopic debridement, and Open if they underwent open debridement. The primary outcome was in-hospital mortality, while secondary outcomes included perioperative complications, home discharge, and resource use. Multivariable regression models were developed to evaluate the association of intervention with clinical and financial endpoints. RESULTS: Of 4, 605 patients who received interventions, 1, 735 (37.6%) were DO, 1, 490 (32.4%) were MIS, and 1, 380 (30.0%) were considered Open. The proportion of DO and MIS increased, while Open declined (2016, 47.0%; 2019, 24.6%; p < 0.001). Compared with Open, MIS had lower rates of abdominal compartment syndrome while having greater rates of preoperative closed drainage (31.9% vs. 13.8%, p < 0.001). After adjustment, odds of in-hospital mortality, respiratory failure, prolonged ventilation, and acute kidney injury were significantly higher in the Open cohort compared with MIS. Hospitalization duration was longer ( β, +12.1 days; 95% confidence interval, 6.8–17.5), and costs were higher ( β, +$58.7K; 95% confidence interval, 33.5–83.9) in Open compared with MIS. CONCLUSION: Minimally invasive approaches for infected pancreatic necrosis have increased over time, while open necrosectomy has declined. Open approaches compared with drainage only or minimally invasive debridement were associated with greater odds of numerous in-hospital complications and resource burden. LEVEL OF EVIDENCE: Prognostic and Epidemiological; Level IV. Abstract :